Lattice-strain induced photophysical properties of NaYF4: Yb3+, Tm3+ upconverting phosphors - Sahoo K.; Ranjan S.; Kumar M. (My University, 2025)
The present work describes the underlying mechanism associated with the synthesis of “NaYF4: Yb3+, Tm3+ upconverting phosphors (UCP)" having diverse morphology (spheres, cubes, hexagonal micro-prism, and micro-rod) as well as enhanced luminescence intensity. Indeed the reported hydrothermal method facilitates an easy and inexpensive strategy for obtaining upconverting phosphors with requisite characteristics through a synergistic combination of substrates and chelating agents, which is the first of its kind. Substrates like ITO, FTO, and plain silica glass (P.G.) are used in synergistic combination with various chelating agents, i.e., EDTA DTPA and EGTA, which ultimately develops nearly hexagonal upconverting phosphors. Overall it is observed that substrate along with chelating ligand coordinates the formation of upconverting phosphors having diverse morphology, while the degree of crystallinity and lattice strain have played crucial role in optimizing the upconversion luminescence. © 2022 Elsevier B.V.